Intelligent teaching toolkit in speech processing utilizing microsoft agent - Tan, Tian Swee, 1978- 483735; Sheikh Hussain Shaikh Salleh, 1958- 455474; Hong, Kai Sze 257901; International Symposium on Information and Communications Technologies (2002 : Selangor) 468677 (Skudai : Universiti Teknologi Malaysia, 2002)
16